Sistem Penjadwalan Lapangan Bola Voli Menggunakan Algoritma Genetika - Ilham Setia Bhakti; Achmad Noeman; Asep Ramdhani Mahbub (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2022)
Scheduling activities are one of the important things to regulate the use of the field, especially at the BTP Sport Center. This study discusses the design of a scheduling application using genetic algorithm rules as a determinant of making a web-based schedule at the BTP Sports Center. Tenants are divided into two categories, namely regular tenants and face-to-face tenants. Permanent tenants are tenants who rent regularly or repeatedly. Field scheduling is important in setting the time and place for exercise. Some of the problems that occur in scheduling are the large number of tenants and the limited number of administrators who set the schedule, especially at the BTP Sports Center. Field schedules have to be paired one by one manually so that sometimes there are schedules that clash with each other without the management realizing it. The genetic algorithm itself is an algorithm inspired by the scientific selection process initiated by the famous scientist Charles Darwin. While the method used for software development is the RAD(Rapid Application Development) method. The administrator will enter the application with the account that has been provided and then enter the names of the tenants and the rental time, after that the schedule can be created automatically to be printed and displayed in the GOR lobby. The result of the research is that by applying genetic algorithms to scheduling, schedules can be mademore efficiently so as to speed up the scheduling process at the BTP Sports Center.